Relations between task delegation and job satisfaction in general practice: a systematic literature review. Issue 1 (December 2016) - Riisgaard, Helle; Nexøe, Jørgen; Le, Jette; Søndergaard, Jens; Ledderer, Loni
Abstract Background It has for years been discussed whether practice staff should be involved in patient care in general practice to a higher extent. The research concerning task delegation within general practice is generally increasing, but the literature focusing on its influence on general practitioners' and their staff's job satisfaction appears to be sparse even though job satisfaction is acknowledged as an important factor associated with both patient satisfaction and medical quality of care. Therefore, the overall aim of this study was 1) to review the current research on the relation between task delegation and general practitioners' and their staff's job satisfaction and, additionally, 2) to review the evidence of possible explanations for this relation. Methods A systematic literature review. We searched the four databases PubMed, Cinahl, Embase, and Scopus systematically. The immediate relevance of the retrieved articles was evaluated by title and abstract by the first author, and papers that seemed to meet the aim of the review were then fully read by first author and last author independently judging the eligibility of content. Results We included four studies in the review. They explored views and attitudes of the staff, encompassing nurses as well as practice managers. Only one of the included studies also explored general practitioners' views and attitudes, hence making it impossible to establish any syntheses on this relation. According to the studies, the staff's overall attitude towards task delegation was positive and led to increased job satisfaction, probably because task delegation comprised a high degree of work autonomy. Conclusions The few studies included in our review suggest that task delegation within general practice may be seen by the staff as an overall positive issue contributing to their job satisfaction, primarily due to perceived autonomy in the work. However, because of the small sample size comprising only qualitative studies, and due to the heterogeneity of these studies, we cannot draw unambiguous conclusions although we point towards tendencies.